2019
DOI: 10.4132/jptm.2018.10.12
|View full text |Cite
|
Sign up to set email alerts
|

PLAG1, SOX10, and Myb Expression in Benign and Malignant Salivary Gland Neoplasms

Abstract: BackgroundRecent findings in molecular pathology suggest that genetic translocation and/or overexpression of oncoproteins is important in salivary gland tumorigenesis and diagnosis. We investigated PLAG1, SOX10, and Myb protein expression in various salivary gland neoplasm tissues.MethodsA total of 113 cases of surgically resected salivary gland neoplasms at the National Cancer Center from January 2007 to March 2017 were identified. Immunohistochemical staining of PLAG1, SOX10, and Myb in tissue samples was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Also, cytoplasm of oncocytoma neoplastic cells is more granular and denser in contrast to the finely foam characteristic cytoplasm of ACC . When cytologically differentiating ACC from other salivary gland neoplasms with oncocytic features SOX10 (SRY‐related HMG‐box 10) and DOG1 (discovered on gastrointestinal stromal tumour 1) are also useful in ruling out negative benign lesions such as WT and oncocytoma from SOX10 and DOG1 immunopositive ACC . However, some benign tumours as PA and basal cell adenoma are also SOX10 immunopositive.…”
Section: Differential Cytopathological and Histopathological Diagnosimentioning
confidence: 99%
See 1 more Smart Citation
“…Also, cytoplasm of oncocytoma neoplastic cells is more granular and denser in contrast to the finely foam characteristic cytoplasm of ACC . When cytologically differentiating ACC from other salivary gland neoplasms with oncocytic features SOX10 (SRY‐related HMG‐box 10) and DOG1 (discovered on gastrointestinal stromal tumour 1) are also useful in ruling out negative benign lesions such as WT and oncocytoma from SOX10 and DOG1 immunopositive ACC . However, some benign tumours as PA and basal cell adenoma are also SOX10 immunopositive.…”
Section: Differential Cytopathological and Histopathological Diagnosimentioning
confidence: 99%
“…However, some benign tumours as PA and basal cell adenoma are also SOX10 immunopositive. Moreover, negative results for SOX10 as well as DOG1 do not favour a benign diagnosis since subgroup of MEC and oncocytic carcinoma is often negative for both markers and DOG1 is negative in both oncocytoma and oncocytic carcinoma …”
Section: Differential Cytopathological and Histopathological Diagnosimentioning
confidence: 99%
“…In salivary gland cytology, immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) are often used to aid diagnosis 3,5,6 . DOG1 and, to a lesser extent, SOX‐10 have been the primary markers of AcCC, although neither is entirely sensitive or specific 7‐14 . Also, AcCC is typically negative for p40 and p63 by IHC 12,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large group of patients with di erent salivary gland tumors was evaluated; the SOX10 expression depended on the histopathological type and presented as below: multiform adenoma -79%, monomorphic adenomas -100%, polymorphic adenocarcinoma of low malignancy -88%, adenoid cystic adenocarcinoma -96% and adenocarcinomas -96%. Moreover, there was no expression of the SOX10 protein in the other subtypes of salivary gland tumors; which means that the determination of the SOX10 protein expression may be a good marker supporting the di erential diagnosis of some tumors subtypes [40,41]. A few studies reported positive SOX10 expression in pheochromocytomas, PEComas and carcinoid carcinomas [42].…”
Section: Sox10 In Other Malignanciesmentioning
confidence: 99%